Does Corporate Social Responsibility Drive Customer Loyalty in Islamic Banking? Evidence from Bank Syariah Indonesia - Adrian, Muhammad Adi (STEI Kanjeng Sepuh Gresik Jawa Timur, 2026)
In recent years, customer preferences have shifted towards more sustainable business practices as awareness of social and environmental issues has increased. This study aims to analyze the influence of Corporate Social Responsibility (CSR) on customer loyalty and to examine the mediating role of company reputation, customer satisfaction, and customer trust in the Islamic banking sector. This study uses a quantitative approach with a survey method of 273 customers of Bank Syariah Indonesia (BSI) KCP Demak Sultan Fattah. The data were analyzed using Structural Equation Modeling (SEM). The results show that CSR has a positive and significant effect on corporate reputation and customer trust, but does not have a significant effect on customer satisfaction. Corporate reputation and customer trust were found to have a positive and significant effect on customer loyalty, while customer satisfaction did not have a significant effect on loyalty. In addition, the mediation test results showed that corporate reputation and customer trust significantly mediated the relationship between CSR and customer loyalty, while customer satisfaction did not play a mediating role. These findings confirm that customer loyalty in Islamic banking is more influenced by trust and institutional reputation than by service satisfaction alone. This study has important implications for strengthening CSR strategies oriented towards building trust and reputation in the Islamic banking industry. theory and practice in the banking industry.